ANALISIS EFEKTIFITAS CEFAZOLINE, CEFTRIAXONE, CEFOTAXIME SEBAGAI ANTIBIOTIK PROFILAKSIS PADA PASIEN SECTIO CAESAREA - Ninik Mas Ulfa; Selly Septi Fandinata; Yuni Hendrawati (As-Syifaa Jurnal Farmasi, 2019)
Prophylactic antibiotics is very necessary in labor with the aim of avoiding infection during SC surgery. This study was descriptive observational with retrospective data collection. The subjects observed in this study were medical records documents of SC patients in RJI hospitals in the area of South Surabaya for the period February - April 2017, with 39 documents were divided into 3 groups. Group A which received Cefazolin, Group B received Ceftriaxone, and Group C which received Ceftaxime. This study was comparison of the effectiveness of these 3 prophylactic antibiotics was measured by temperature parameters, leukocytes and observation of the condition of the surgical wound. Based on statistical analysis using the Kruskal Wallis test, it was found that the effectiveness of antibiotic prophylaxis Cefazolin was more effective in reducing the temperature and leukocytes of SC patients compared to Ceftriaxon and Cefotaxim, with an average rating of Cefazolin in temperature parameters of 27.58 and an average ranking in leukocyte parameters ie 25.81. Meanwhile in observing surgical wounds from three groups of antibiotic prophylaxis there was no redness, no swollen wounds, no discharge and no pus from surgical wounds